Secrets of persuasion - Moss, Geoffrey (Thomson, 2007)
Discover the communication secrets used by successful and influential people. Today's successful people are those who can communicate well and get their ideas accepted. Learn the communication secrets used by successful and influential people. Learn the art of influencing people. Learn ways to improve presentations. So you can write to convince, speak with confidence, publicise your activities, run effective meetings, negotiate successfully, display your products with flair and improve your corporate image